1996
DOI: 10.1159/000282919
|View full text |Cite
|
Sign up to set email alerts
|

Double-Pigtail Stents for Distal Ureteral Calculi: An Alternative Form of Definitive Treatment

Abstract: In this study, we treated patients with a solitary distal ureteral stone of less than 10 mm in maximum diameter by placing a double-pigtail stent and subsequently removing it allowing the calculus to pass spontaneously. A total of 40 patients were enrolled in the study with a mean stone size of 5.1 × 3.5 mm (range 2–8 mm in length and 2–7 mm in width). The indication for intervention was intractable pain in 5 patients, infection due to obstruction in 2, highly obstructed urinary tract in 10, absence of progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Several studies have been published assessing the ability of ureteral stents to facilitate stone passage. These investigators concluded that calculi of up to 10 mm in size located in the distal ureter will pass 83±85% of the time after insertion of an internal ureteral stent [19,20]. Conversely, investigators from Ireland determined that in a canine model, stone passage from the proximal ureter may be limited due to reduced motility effects of the stent on the ureter.…”
Section: Spontaneous Passage Of Ureteral Stonementioning
confidence: 99%
“…Several studies have been published assessing the ability of ureteral stents to facilitate stone passage. These investigators concluded that calculi of up to 10 mm in size located in the distal ureter will pass 83±85% of the time after insertion of an internal ureteral stent [19,20]. Conversely, investigators from Ireland determined that in a canine model, stone passage from the proximal ureter may be limited due to reduced motility effects of the stent on the ureter.…”
Section: Spontaneous Passage Of Ureteral Stonementioning
confidence: 99%
“…The most important advantage of stent placement is prevention of ureteral obstruction; hence, occurrence of renal colic that may arise from ureteral edema or passage of stone fragments. [1][2][3] Also, ureteral dilation caused by stents may ease the passage of small stone particles. It is proposed that other advantages of the application of stents are quicker healing of the ureter and prevention of ureteral strictures.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that other advantages of the application of stents are quicker healing of the ureter and prevention of ureteral strictures. 2,3 An impacted ureteral stone is variably considered either as a condition in which a stone remains at the same site for more than 2 months 4 or the inability to pass a guidewire or catheter on initial attempts. 5 Many ureteroscopic procedures can be classified as uncomplicated.…”
Section: Introductionmentioning
confidence: 99%
“…Deliveliotis et al [3] investigated 40 patients with a mean stone size of 5.1 ! 3.5 mm fluoroscopically who were stented under local anesthesia for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Although distal stones can be managed with extracorporeal shock wave lithotripsy (ESWL) or ureteroscopy, studies exist in which indwelling ureteral stents, placed under local anesthesia, have been utilized as a definitive therapy for small distal ureteral calculi [3]. Historically, such stents have been used as a temporary modality of treatment to relieve obstruction.…”
Section: Introductionmentioning
confidence: 99%